LEADERSHIP INFLUENCE ON TEACHER ENGAGEMENT AND PROFESSIONAL RESPONSIBILITY - Kamila Ruzieva (Bright Mind Publishing, 2025)
Leadership influence on teacher engagement and professional responsibility is a critical factor in the effectiveness and sustainability of contemporary educational organizations. This article examines how leadership practices shape teachers’ involvement in professional activity and their orientation toward responsibility beyond formal accountability. Drawing on classical and modern theories of educational leadership, the study analyzes transformational, distributed and instructional leadership approaches as key mechanisms for fostering trust, shared meaning, autonomy and professional growth. Based on a theoretical and comparative analysis of international research, the article demonstrates that leadership affects educational outcomes primarily through its impact on teachers’ psychological engagement, sense of ownership and ethical commitment to student learning. The findings highlight that leadership oriented toward dialogue, participation and capacity building creates conditions in which professional responsibility becomes internalized and sustainable, while purely administrative and control-based models tend to generate compliance rather than genuine engagement. The article argues that strengthening leadership competencies is essential for building learning-oriented school cultures and improving the long-term quality of education.
Keywords: Educational leadership, teacher engagement, professional responsibility, transformational leadership, distributed leadership, instructional leadership, educational management.